The Strategy Improvement To Increase The Customer Retention Of TipTop Supermarket & Department Store Rawamangun In East Jakarta - Agam, Fadhil Ghalib; Aprianingsih, Atik (The Indonesian Journal of Business Administration, 2015)
Abstract. TipTop is a business network that engaged in the field of supermarket & department store where one of its branches is located in Rawamangun, East Jakarta. TipTop Rawamangun provides basic human needs products such as groceries and clothes. They sell their products directly only at the store. TipTop Rawamangun started to operate in 1979 and it is still running until today. In general, their sales still have been running quite smoothly until now, but for the future they should begin to be vigilant against the threats of their competitors due to the fact that each year the outlets of the competitors continue to multiply. It makes the people become having more options to choose where to shop. This condition has the potency to turn off the TipTop Rawamangunâ€™ business in the future. To maintain its business, TipTop Rawamangun needs to increase the customer retention, so they want to know in detail about what are the priorities of customers in choosing the stores to shop. TipTop Rawamangun wishes to know the will and desires of customers, so they are able to prepare some strategies to make their existing customers unwilling to stop shopping at their store for the sake to go shopping somewhere else. The business situation analysis begins by analyzing the internal and external environment. Internal analysis consists of â€˜Value Chain Analysisâ€™, â€˜STP Analysisâ€™, and â€˜Marketing Mix 7P Analysisâ€™. While the external analysis consists of â€˜PESTLE Analysisâ€™, â€˜Porterâ€™s Five Forces Analysisâ€™, â€˜Competitor Analysisâ€™, and â€˜Customer Retention Influencing Factors Analysisâ€™. The result of those internal and external analysis is the TipTop Rawamangunâ€™s â€˜SWOT Analysisâ€™. To discover the opinions and desires of customers towards TipTop Rawamangun, the author distributed questionnaires to TipTop Rawamangunâ€™s 286 customers as samples to determine whether the customers are satisfied with the services at TipTop Rawamangun or not. The results of the questionnaires indicate that the value of TipTop Rawamangunâ€™s customer retention is just â€œModerateâ€ (Mean = 3.12) and reveal that several sectors should be enhanced in TipTop Supermarket & Department Store, Rawamangun, East Jakartaâ€™s business.Â Keywords: Customer Retention, Supermarket Business, Retail Industryâ€™s Growth.